Potomorphological Characteristics of Femural Head Structures in Patients of Different Ages Infected with Covid-19 - Jumanov Ziyadulla Eshmamatovich; Khudayberganov Sadiq Toshtemirovich (Genius Journals, 2024)
In the article, the photomorphological characteristics of femoral head structures of patients of different ages infected with COVID-19 were studied. Also, patient R. 28 years old, surgery was performed, hydropic dystrophy of chondrocytes in the femoral head tissue, slight thinning of the femoral head, was sufficiently studied by Hematoxylin-eosin, and conclusions and recommendations were given accordingly.
Keywords: Femoral head; COVID-19